Chloroplast characterizations of a Phalaenopsis native to China, Phalaenopsis mannii (Orchidaceae). Issue 3 (2nd July 2020) - Chen, Bin; Zhang, Yanping; Cao, Yinghui; Zheng, Yan; Wei, Ziling; Zhao, Kai; Peng, Donghui; Zhou, Yuzhen
ABSTACT: Phalaenopsis mannii, one of the native Phalaenopsis in China, is an important parent for breeding new varieties. However, its position has been unclear in Phalaenopsis . The obtained high-quality P. mannii chloroplast genome will provide useful information for phylogenetic and future breeding of Phalaenopsis . Herein, we reported a complete chloroplast genome of P. mannii from Yunnan, China. The sequencing data obtained from BGISEQ-500 platform were assembled. This sequence had a circular molecular length of 148, 596 bp and contained a total of 127 genes with an average GC content of 36.7%. Phylogenetic analysis indicated that Phalaenopsis was monophyletic with strong support, in which the P.mannii was the sister-group of Phalaenopsis aphrodite subsp. formosas, Phalaenopsis 'TinyStar' and Phalaenopsis equestris .